The Negative Animal - Timofeeva, Oxana (Stasis, 2013)
In this paper, I analyze some aspects of Hegelian and post- Hegelian thought in order to demonstrate how the concepts of animality and negativity intersect in philosophical reflections on nature. In the first part, I consider the figure of the animal in Hegel’s work and show its necessary relation to negativity. In the second part, I return to Georges Bataille and Alexander Kojève’s discussion of the end of history, where negativity appears with a human face, as something that leaves animals behind. Finally, in the third part, I justify the animal’s claims on negativity as a force of transformation and change through a peculiar political ontology of the fish.